Fluorescent probe with aggregation-induced emission characteristics for targeted labelling and imaging of cancer cells. Issue 19 (13th February 2017) - Peng, Na; Xu, Rui; Si, Michelle; Victorious, Amanda; Ha, Emily; Chang, Chun-Yu; Xu, Xiao-Ding
Abstract : We report a new peptidyl boronic acid-based fluorescent probe with an AIE characteristic. The probe shows the ability to target, label and image cancer cells via specific recognition between the boronic acid group and cancer-associated sialic acid. Abstract : We report a new peptidyl boronic acid-based fluorescent probe with an aggregation-induced emission (AIE) characteristic. Through specific recognition between the boronic acid group and the cancer-associated sialic acid (SA), this fluorescent probe shows an ability for targeted labelling and imaging of cancer cells.